A Phenomenological Analysis on the Influence of Faith in Patients' Treatment and Recovery. (Revista Brasileira Multidisciplinar, 2008)
The research brings visions and points of view on the issue of faith. The investigation of this question has taken place in a health institution that treats patients with infectious diseases, where we could examine the influence of faith in the treatment and recovery of inpatients and the view of some health care professionals within the same institution. The theoretical and phenomenological approach has been adopted in the present study.
Keywords: Psychosocial Aspect; Faith; Health-illness; Hospitalization; Phenomenology.